Application of Salvage Autologous Blood Transfusion for treating Massive Hemorrhage during Ectopic Pregnancy - Li, Junying; Jin, Hequn; Hu, Zhen (Frontiers in Surgery, 2022)
Purpose: To explore the application value of salvage autologous blood transfusion in massive hemorrhage in ectopic pregnancy. Methods: A retrospective analysis was performed on the clinical data of patients in our hospital from January 2019 to December 2021 who were confirmed to be massive hemorrhage from an ectopic pregnancy during surgery and were treated with blood transfusion. Patients were divided according to their transfusion method into an autologous group treated with recycled autologous transfusion (n=46), a mixed group treated with recycled autologous + allogeneic transfusion (n=28), and an allogeneic group treated with allogeneic transfusion (n=41). The volume of intra-abdominal bleeding, the volume of autologous and allogeneic blood transfusion; blood transfusion reaction and postoperative fever. Results: In terms of intra-abdominal bleeding volume, the autologous and mixed groups were higher than the allogeneic group (P<0.05), and there was no statistical difference between the autologous and mixed groups (P>0.05). In terms of autologous blood transfusion volume, the autologous group was higher than the mixed group (P<0.05). In terms of allogeneic blood transfusion volume, the allogeneic group was higher than the mixed group (P<0.05). After blood transfusion treatment, the postoperative fever rates were 4.35%, 10.71%, and 19.51% in the autologous, mixed, and allogeneic groups, respectively, and the blood transfusion reaction rates were 0.00%, 3.57%, and 9.76%, respectively, which were lower in the autologous group than in the allogeneic group (P<0.05). At 30 min after blood transfusion, SBP, DBP and SpO2 were higher in all three groups than before blood transfusion (P<0.05), and HR was lower than before blood transfusion (P<0.05), but there was no statistically significant difference between groups at 30 min after blood transfusion (P>0.05). At 24h postoperatively, there was no statistical difference in the comparison of HCT, Hb, PLT, and RBC among the three groups (P>0.05) Conclusion: The use of recycled autologous blood transfusion for massive hemorrhage in ectopic pregnancy is a safe and feasible method for rescuing patients with massive hemorrhage in ectopic pregnancy because it can rapidly replenish the patient's blood volume and save blood resources without causing postoperative hemodynamic, blood routine and electrolyte abnormalities.